Proposal for a psychoeducational program of coping strategies for parenting stress addressed to parents and parents representatives (Boletin Médico de Postgrado, 2020)
The purpose of this research was to propose a psychoeducational program to develop parenting stress strategies for parents and parent’s representative of children that attend the children's psychology office of the Hospital Militar Dr. José Ángel Álamo. The sample included 40 subjects that attended the consult in the January-February 2018 period. In the diagnostic phase, the presence of parenting stress and coping strategies was determined through the application of a modified questionnaire using the Parental Stress Test (Abidin) and the Coping Strategies Test (Carver). The results showed that 54% of participants had an inadequate psychological functioning, 65% had absence of personal resources and 53% had social and family support The majority of subjects had adequate coping strategies which included conflict resolution, search for social support, reevaluation, afective regulation and search for information. The feasibility study provided favorable results to design a psychoeducational program to develop coping stress strategies in the form of four (04) theoretical-practical workshops which will provide parents with tools to understand the nature of their role, the neurodevelopment of children and positive discipline strategies.
Keywords: parental stress; Parental Stress Test; Coping Strategies Test